1998
DOI: 10.1088/0963-0252/7/3/018
|View full text |Cite
|
Sign up to set email alerts
|

Ionization efficiency in a geometrically pinched cascaded arc

Abstract: Remote deposition allows separate optimization of the plasma production source and of the deposition process. To improve the ionization performance of the source, an argon cascaded arc plasma is studied by simulations. Improvements of the source performance in ion yield are achieved by constricting the bore of the arc channel near the entrance. Such a geometrical pinch construction leads to a higher neutral density at the arc inlet which results in increased ionization in the cascaded arc. The improved ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
32
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 29 publications
5
32
0
Order By: Relevance
“…[ [25][26][27][28][29][30]. Salient additions for this work include the wall heat transport module and algorithmic changes to improve the treatment of plasmas with very high ionization degree.…”
Section: E the Codementioning
confidence: 99%
“…[ [25][26][27][28][29][30]. Salient additions for this work include the wall heat transport module and algorithmic changes to improve the treatment of plasmas with very high ionization degree.…”
Section: E the Codementioning
confidence: 99%
“…Accurate EII cross sections (EIICSs) for ground and excited states of atoms and molecules are important in modeling arcs [4], discharges [5], plasmas [6], the solar atmosphere [7] and astrophysical media [8], as well as in spectroscopy [9] of ionized media and benchmarking theoretical predictions [10]. Most EII studies have involved ground states [1,2].…”
mentioning
confidence: 99%
“…Ionization thresholds for low lying target states studied to date were several eV, and EIICSs had magnitudes of several 10 ÿ16 cm 2 . High Rydberg states (HRSs) of atoms and molecules, e.g., having n 30, exist alongside low-energy electrons in most plasmas of laboratory, upper atmosphere, astrophysical, and technological interest [1][2][3][4][5][6][7][8][9]. HRSs have binding energies much less than 1 eV and act as excellent electron donors [3].…”
mentioning
confidence: 99%
“…13 The measured 16% ionization efficiency again supports postsource heating. We demonstrated that this combination leads to significant power dissipation in the plasma outside the source.…”
mentioning
confidence: 70%